African American Muslims under Barack Obama’s Post-black Politics - DAKHMOUCHE, Amina (Journal of Human Sciences, 2025)
The election of Barack Obama was an unprecedented event that triggered scholarly research and excited cultural and racial critics about the factors that contributed to the election of an African American president. “Post-blackness” is a philosophy that intends to explain the complexities of Obama’s personality as well as signals the end of traditional blackness in favor of a more fluid and boundless black identity that Obama personifies. This identity relies on multilingualism that rejects black authenticity and rejects historical ties to the cultural trauma that held back the African American community. This article offers a qualitative analysis of Barack Obama’s Post-black politics which were characterized by deracialization, neutrality and inclusivity but did not achieve the expected impact on the Muslim African American community. Moreover, Obama’s attitude towards Islam in America did not reflect a Post-black policy of racial justice; rather, it held the position of the previous administration, both in terms of domestic and foreign affairs. Obama’s Post-black aesthetic did not impact his political agenda, which led to the general deception of both Sunni and unorthodox Black American Muslims.